New Wrapped Distribution via Richard Link Function - Demirelli, Arzu Ekinci; Gurcan, Mehmet (Amer Inst Physics, 2017)
In this paper, we investigate a new wrapped distribution obtained from Richard link function. In the literature, many probability distributions are used wrapped form via normal, Cauchy, etc.. In this point, the most important characteristic of the Richard link function is that the flexible. Because of this feature Richard link function is useful. But, the Richard link function does not have a distribution form and analytical solution of parameter estimation. In this study we examined properties of wrapped Richard distribution and we have sampled for ant data.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 19-25, 2016 -- Rhodes, GREECE
Keywords: Wrapped distribution; Richard growth curve; Link function